Effects of Dietary Energy and Protein on Growth Performance and Carcass Quality of Broilers during Starter Phase - Niu, Zhuye; Shi, Jingsong; Liu, Fuzhu; Wang, Xianhui; Gao, Chunqi; Yao, Likai (International Journal of Poultry Science, 2009)
A 3x4 factorial arrangement with three Metabolizable Energy (ME) levels (12.13, 12.55, 12.97 MJ/kg) and four Crude Protein (CP) levels (20.0, 21.0, 22.0 and 23.0%), respectively, was undertaken to investigate the influence of varying levels of dietary energy and protein on broiler performance and carcass quality from 1-21 d aysof age. Six hundred 1 day old broiler chicks were randomly divided into 12 treatments, each of which had five replicates of 10 birds. BW of 21 days of age was significantly increased with an increase in dietary ME (p<0.05), while not influenced by dietary CP (p>0.05). Both ME and CP significantly improved feed efficiency (P<0.05). ME significantly affected on feed intake, while CP not affected. However, there were no significant interaction in BW, average daily gain, feed intake and feed efficiency between dietary ME and CP. Higher level of dietary ME (12.97 MJ/kg) significantly increased abdominal fat percentage when compared with lower ME (12.13MJ/kg or 12.55 MJ/kg). L* of leg meat was decreased by dietary ME, while L* of breast meat was not affected. a* of both breast meat and leg meat was increased with increasing dietary ME and CP. b* of leg meat was decreased by ME while b* of breast meat was not affected. Water-holding capacity (WHC) of breast meat was decreased by dietary ME, while increased by dietary CP. The results of present research indicated that the optimal dietary ME requirement of broilers from 1-21 days of age is 12.97 MJ/kg and the CP requirement is 21-22%.